High school students' spatial ability and creativity in geometry - Guzel, Nuran; Sener, Ersin (ELSEVIER SCIENCE BV, 2009)
The focus of this study is to investigate low and high spatial ability students' potential creativity in geometry. Students were member of Anatolian and State High Schools, in Marmara region of Turkey. Purdue spatial ability, a likert scale instrument (P SA, 2003) and geometry problem set have been used to collect the data. Findings showed that students in state schools have low spatial ability levels than the Anatolian Students. Furthermore, Anatolian students and State School creativity levels were not different with easy geometry problems. (C) 2009 Elsevier Ltd. All rights reserved
Keywords: spatial ability; creativity; geometry; high school; Education & Educational Research